Clinical and Genetic Features of Chinese Adult Patients With Chronic Non-Bacterial Osteomyelitis: A Single Center Report - Zhao, Mengzhu; Wu, Di; Yu, Keyi; Shen, Min (Frontiers in Immunology, 2022)
Objectives: Chronic non-bacterial osteomyelitis (CNO) is a rare polygenic autoinflammatory bone disease. We aimed to characterize the clinical manifestations and gene variants of Chinese adult patients with CNO. Methods: By reviewing data of all CNO patients being diagnosed and followed up at the Center for Adult Autoinflammation Diseases, Department of Rheumatology, Peking Union Medical College Hospital, clinical and genetic features of these patients were evaluated and concluded. Results: The median age of disease onset was 19 (6-64) years old, and adult-onset was observed in 6 (60%) patients. The mean time of diagnosis delay was 92±78 months. The common symptoms were bone pain (10, 100%), fever (9, 90%), and arthritis (6, 60%). In total, there were 54 skeletal lesions, and each patient had no less than 2 lesions. The most frequently affected sites included lower limbs (20.5%), mandible, vertebrae and pelvis (17.5%, separately). Variants of 4 genes were detected in our study including COL1A1, PSTPIP1, LRP5 and CLCN7. A combination therapy containing tumor necrosis factor (TNF) ɑ inhibitors was proved to be effective. Conclusion: This is the first and largest case series of CNO in Chinese adult patients. Four novel genetic mutations potentially associated with CNO were identified. Notably, CNO should be considered in the differential diagnosis of adult patients with long disease course and recurrent multifocal osteomyelitis of unknown cause, and these patients might benefit from combination therapy containing TNFɑ inhibitors.